2019
DOI: 10.3390/nano9040532
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Nanofibers for Therapeutics Delivery

Abstract: The limitations of conventional therapeutic drugs necessitate the importance of developing novel therapeutics to treat diverse diseases. Conventional drugs have poor blood circulation time and are not stable or compatible with the biological system. Nanomaterials, with their exceptional structural properties, have gained significance as promising materials for the development of novel therapeutics. Nanofibers with unique physiochemical and biological properties have gained significant attention in the field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(139 citation statements)
references
References 141 publications
(169 reference statements)
1
138
0
Order By: Relevance
“…The electrosprayed mat eliminated P. aeruginosa bacterial colonies within three days of daily dressing changes in an in vivo full-thickness excisional wound treated initially by debridement [110]. These recent studies suggest excellent wound treatment using nanofibers; however, their use in clinical practice is limited due to toxicity, large-scale production, and ability to control capacity and functionality [206].…”
Section: Nanoscale Materialsmentioning
confidence: 99%
“…The electrosprayed mat eliminated P. aeruginosa bacterial colonies within three days of daily dressing changes in an in vivo full-thickness excisional wound treated initially by debridement [110]. These recent studies suggest excellent wound treatment using nanofibers; however, their use in clinical practice is limited due to toxicity, large-scale production, and ability to control capacity and functionality [206].…”
Section: Nanoscale Materialsmentioning
confidence: 99%
“…Moreover, the authors reported that viability can be correlated with the hydrophobicity and to the extreme length of lactic acid bacteria, whereas a horizontal or vertical electrospinning set-up did not have any role. Development of nanofibers via electrospinning has a great potential and use in pharmaceutical and food industry for their properties i.e., sterile nature, biocompatibility, adhesiveness, efficiency, and as vehicle for controlled and sustained release in drug delivery [179][180][181][182]. Electrospinning and electrospraying represent innovative technologies for the delivery of nutraceuticals [183].…”
Section: Type Activity Study Referencesmentioning
confidence: 99%
“…The majority of delivery routes investigated over the years to provide the administration of drug molecules by electrospun systems, including oral, buccal, etc. For example, macro-and micromolecules captured in nanofibers as film-based DDS were delivered by oral route, and electrospun scaffolds have delivered proteins or vaccines by buccal or sublingual route and has also been used to prepare electrospun scaffolds as ocular inserts to treat inflammation or infections [11]. Moreover, the technique has been used to integrate a number of key drugs, such as ampicillin, cefoxitin, tetracycline, and triclosan into FDA-approved polymers (natural or synthetic).…”
Section: Electrospinningmentioning
confidence: 99%